PENGARUH PERMAINAN GALAH HADANG TERHADAP PERILAKU PROSOSIAL ANAK - Nafisa, Hidayatun; Samad, Munawwarah (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study investigates the influence of the traditional game Galah Hadang on the prosocial behavior of children aged 5–6 years at RA Zuhratul Aini. The research was motivated by the limited social interaction and prosocial skills observed among young children. A quantitative approach was employed using a one-group pretest–posttest experimental design involving 16 participants. Data were collected through systematic observation and analyzed using the Shapiro–Wilk normality test and paired sample t test. The findings revealed a significant improvement in prosocial behavior following the implementation of Galah Hadang, with a p-value < 0.05. These results demonstrate that the game effectively enhances children’s cooperation, responsibility, respect, sharing, and tolerance. The study underscores the pedagogical value of traditional games, suggesting their potential as engaging and culturally relevant learning media to foster social development in early childhood education.